Inhibition of caspase 1 reduces human myocardial ischemic dysfunction via inhibition of IL-18 and IL-1β - Pomerantz, Benjamin J. (The National Academy of Sciences, 2001)
The proinflammatory cytokine IL-18 was investigated for its role in human myocardial function. An ischemia/reperfusion (I/R) model of suprafused human atrial myocardium was used to assess myocardial contractile force. Addition of IL-18 binding protein (IL-18BP), the constitutive inhibitor of IL-18 activity, to the perifusate during and after I/R resulted in improved contractile function after I/R from 35% of control to 76% with IL-18BP. IL-18BP treatment also preserved intracellular tissue creatine kinase levels (by 420%). Steady-state mRNA levels for IL-18 were elevated after I/R, and the concentration of IL-18 in myocardial homogenates was increased (control, 5.8 pg/mg vs. I/R, 26 pg/mg; P < 0.01). Active IL-18 requires cleavage of its precursor form by the IL-1β-converting enzyme (caspase 1); inhibition of caspase 1 also attenuated the depression in contractile force after I/R (from 35% of control to 75.8% in treated atrial muscle; P < 0.01). Because caspase 1 also cleaves the precursor IL-1β, IL-1 receptor blockade was accomplished by using the IL-1 receptor antagonist. IL-1 receptor antagonist added to the perifusate also resulted in a reduction of ischemia-induced contractile dysfunction. These studies demonstrate that endogenous IL-18 and IL-1β play a significant role in I/R-induced human myocardial injury and that inhibition of caspase 1 reduces the processing of endogenous precursors of IL-18 and IL-1β and thereby prevents ischemia-induced myocardial dysfunction.